BlackBerry [videorecording (DVD)] - Johnson, Matt, 1985-; Johnson, Matt, 1985-; Miller, Matthew, (Producer); Baruchel, Jay, 1982-; Howerton, Glenn, 1976-; Sommer, Rich, 1978-; Ironside, Michael, 1950-; Donovan, Martin, 1957-; Giroux, Michelle, 1976-; Rubinek, Saul, 1948-; Elwes, Cary, 1962-; McNish, Jacquie (IFC Films, 2023)
The "true story" of the meteoric rise and catastrophic demise of the world's first smartphone, BLACKBERRY is a whirlwind ride through a ruthlessly competitive Silicon Valley at breakneck speeds.